The role of volition in human conditioning - Rathna N; Rangasayee R (Journal of All India Institute of Speech and Hearing, 1970)
The importance and application of Behaviour Therapy is well established . in the treatment of learning disorders. However, the principles of Behaviour Therapy are borrowed from animal experiments based on learning theory which were originally and mainly patterned after animals experiments. The reasons for this preponderance of animal experiments over human experiments are obvious. Animal experiments are cheaper, faster and most importantly they are most practical because it is easier to control the subjects, the conditions or environment and the experimental procedures in animal experiments than in human experiments. Also animal experiments involve fewer ethical and moral questions. There are now a number of human experiments which are being conducted; in fact it has even been held that each controlled therapy session is an experiment.